Gender Differences in EFL Coursebook Used in Islamic School of Bengkulu Province - Hadianto, Arief (UNIB Press, 2022)
This study aims to see if there is a gender bias in the English textbooks for EFL used by Islamic schools in Bengkulu province. The objects of the research used are the course books used in Islamic schools in Bengkulu city, entitled